2014
DOI: 10.1111/apa.12554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light on metalloporphyrin-treated newborn mice

Abstract: The use of polymeric particulate delivery systems can improve the stability and enhance intestinal absorption of ZnPP, while retaining HO inhibitory potency without photosensitising effects, and thus is potentially useful in treating neonatal hyperbilirubinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In addition, ZnPP-Lipid had no inhibitory effect on brain, a nontarget organ, consistent with it not crossing the blood/brain barrier at those doses. In regards to photosensitivity, we have previously shown that even at a dose of 60 µmol/kg BW, ZnPP-Lipid (and the lipid vehicle alone) was not phototoxic to newborn mice exposed to fluorescent light (21). Furthermore, Maines have shown that ZnPP does not alter the other enzymatic activities, such as δ-aminolevulinate synthetase and cytochrome P-450, in the rat spleen and liver (7).…”
Section: Articlesmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, ZnPP-Lipid had no inhibitory effect on brain, a nontarget organ, consistent with it not crossing the blood/brain barrier at those doses. In regards to photosensitivity, we have previously shown that even at a dose of 60 µmol/kg BW, ZnPP-Lipid (and the lipid vehicle alone) was not phototoxic to newborn mice exposed to fluorescent light (21). Furthermore, Maines have shown that ZnPP does not alter the other enzymatic activities, such as δ-aminolevulinate synthetase and cytochrome P-450, in the rat spleen and liver (7).…”
Section: Articlesmentioning
confidence: 98%
“…We first determined the peak inhibitory potency of ZnPPLipid in 4-d-old mice, by measuring liver HO activity at 1.5, 3, 6, and 12 h after IG administration of 30 µmol/kg body weight (BW) of ZnPP-Lipid, a dose we previously showed that significantly inhibits native liver HO activity in mice (21). We found that liver HO activity was significantly inhibited to 69 ± 6% (215 ± 19 pmol/h/mg fresh weight (FW), P < 0.01) and 73 ± 12% (229 ± 36 pmol/h/mg FW, P < 0.01) of control levels at 3 and 6 h, respectively, after ZnPP-Lipid administration (Figure 1).…”
Section: Determination Of Peak Inhibitory Potency Of Znpp-lipidmentioning
confidence: 99%
See 3 more Smart Citations